The simulation model of HVDC transmission system / Nor Afiza Rashid - Rashid, Nor Afiza (2007)
This thesis reports the performance and control characteristic of an HVDC transmission using simulation software. A software simulation of HVDC using PSIM software was developed. In order to study the characteristic of the HVDC system two types of HVDC have been model using the PSIM software. The monopolar and bipolar types of high voltage were investigated. The converters at both end are function in rectifier and inverter which determine by the firing angle of the thyristor. The performances of both converters were demonstrated. The main objective of HVDC converter is to provide point to point electrical power interconnection between asynchronous ac power networks. Advancements in power electronics are making High Voltage Direct Current (HVDC) Transmission System more attractive and reliable. More can be obtained from huge investment in complex HVDC system if operation and maintenance personnel have deeper understanding about the function of this system.